Farey Sequence for Error Correcting Codes and Medical Images - Poornima, M; Jagannathan, S; Chandrasekhar, R; T Kumara, S (International Journal of Engineering and Technology, 2018)
A new scheme for Error Correcting Codes and the coding of medical images through Farey Sequence is brought in the paper. It brings out the reduced real point representations and more of integer point representations. The test case and outcomes are explained in the section 4 and 5.Â Â